Tinjauan Pustaka: Pengaruh Kesadaran Wajib Pajak, Sanksi Pajak, Sosialisasi Pajak, Pengetahuan Pajak, Kualitas Pelayanan Pajak terhadap Kepatuhan Wajib Pajak - Ardiyanti, Anita; Murniadi, Murniadi; Suparman, Suparman; Abbas, Dirvi Surya (GEMILANG: Jurnal Manajemen dan Akuntansi, 2025)
Tax revenue is a vital instrument for a country's economic development. However, low levels of taxpayer compliance in fulfilling tax obligations remain a persistent challenge. Several factors may influence this behavior, including taxpayer awareness, tax sanctions, the extent of tax socialization, tax knowledge, and the quality of tax services. This study employs bibliometric analysis to systematically map the landscape of tax compliance research. VOSviewer software is utilized for its efficiency and safety in managing extensive bibliographic data and its ability to generate insightful visualizations. The analysis produces an overlay visualization that highlights the temporal distribution of keywords, as well as a density visualization that reveals the concentration of research efforts in various thematic areas. The findings indicate that tax compliance is still a broad and evolving research topic with significant potential for further investigation.